Pharmacological inhibition of the chemokine C‐C motif chemokine ligand 2 (monocyte chemoattractant protein 1) accelerates liver fibrosis regression by suppressing Ly‐6C+ macrophage infiltration in mice. Issue 3 (30th January 2014) - Baeck, Christer; Wei, Xiao; Bartneck, Matthias; Fech, Viktor; Heymann, Felix; Gassler, Nikolaus; Hittatiya, Kanishka; Eulberg, Dirk; Luedde, Tom; Trautwein, Christian; Tacke, Frank
<x xml:space="preserve">Abstract</x> Macrophages constitute a major proinflammatory component during chronic liver diseases and are considered a key factor in promoting hepatic fibrosis. However, there is increasing evidence that distinct monocyte and macrophage subsets exert critical functions in regression from organ fibrosis as well. Experimental mouse models of fibrosis regression have identified "restorative" macrophages as Ly‐6C (Ly6C, Gr1) low‐expressing, monocyte‐derived cells. We investigated molecular pathways balancing proinflammatory and restorative macrophages during fibrosis regression as well as pharmacologically augmenting beneficial macrophage functionality in fibrosis resolution. Therefore, we employed a Spiegelmer‐based inhibitor of the chemokine, C‐C motif chemokine ligand 2 (CCL2; monocyte chemoattractant protein 1), termed mNOX‐E36, in the regression phase of two murine models of toxic (CCl4) and metabolic (methionine‐choline–deficient diet) liver fibrosis. Although inflammation rapidly declined after cessation of injury, we observed a transient influx of Ly‐6C+ infiltrating monocytes (iMΦ), which are characterized by typical macrophage morphology, up‐regulated expression of CCR2, and the pro‐inflammatory cytokine, tumor necrosis factor (TNF), in injured liver. By inhibiting the early influx of Ly‐6C+ iMΦ by the CCL2 inhibitor, mNOX‐E36, the intrahepatic macrophage equilibration shifted toward the "restorative" Ly‐6C‐ subset of iMΦ. Consequently, fibrosis resolution was significantly accelerated upon mNOX‐E36 administration in both models. Blocking transient recruitment of infiltrating Ly‐6C+ monocytes, but not direct effects of the inhibitor on the remaining macrophages, resulted in reduced intrahepatic levels of proinflammatory cytokines. Conclusion: Transient CCL2‐dependent recruitment of infiltrating Ly‐6C+ monocytes during fibrosis regression counteracts scar resolution by perpetuating inflammatory reactions through release of proinflammatory cytokines such as TNF. Pharmacological inhibition of Ly‐6C+ monocyte recruitment using the CCL2‐inhibitor, mNOX‐E36, accelerates regression from toxic and metabolic liver fibrosis in two independent experimental models. (Hepatology 2014;59:1060–1072)